Family incivility, emotional exhaustion, and hotel employees outcomes: a moderated mediation model - Zhen, Yan; Mansor, Zuraina; Wei, Chong Choo (Emerald Publishing Limited, 2023)
Purpose This study aims to analyze the impact of family incivility (FI) on in-role performance (IRP) and proactive customer service performance (PCSP) via the mediating effect of emotional exhaustion (EE) and the moderating roles of emotional intelligence (EI) and mindfulness. Design/methodology/approach Hypotheses were verified using multisource and multiwave data collected from 337 valid hotel employee–supervisor dyads in Kuala Lumpur, Malaysia. Data were analyzed using SPSS 24.0, AMOS 24.0 and PROCESS (version 3.4). Findings FI intensified frontline employees’ (FLEs) EE, which subsequently impeded their IRP and PCSP. EI and mindfulness moderated the direct influence of FI on EE, IRP and PCSP and moderated the indirect influence of FI on the two aforementioned outcomes through EE. Practical implications Managers should observe FLEs’ indicators of FI and deter its emergence by implementing care programs for FLEs suffering from FI. In addition, human resource managers should preferentially recruit employees with high EI through related tests. Hotels can invite reputable psychologists to provide psychotherapy interventions for FLEs, such as mindfulness-based psychological lectures and therapy. Originality/value The hospitality literature lacks an understanding of the underlying process through which FI affects FLEs’ job outcomes. This study incorporates EE as a mediator of the FI’s impact on IRP and PCSP, and to the best of the authors’ knowledge, this study is the first to assess whether EI and mindfulness moderate the direct impact of FI on IRP and PCSP and the indirect impact of FI on two aforementioned outcomes via EE.